Management of Development and Financing of Preachers by Wahdah Islamiyah Medan - Muhammad Yakub; Muniruddin Muniruddin (Sekolah Tinggi Agama Islam YDI Lubuk Sikaping, 2026)
This study aims to analyze the management of da'wah development and financing implemented by Wahdah Islamiyah Medan and identify supporting and inhibiting factors. The study used a descriptive qualitative approach with a case study design. Data were obtained through in-depth interviews with regional administrators and delegated da'wah delegates, observations of development activities, and organizational documentation. Data were analyzed through condensation, presentation, and conclusion drawing, while their validity was tested through triangulation of sources and methods. The results indicate that the effectiveness of Wahdah Islamiyah Medan's da'wah program is supported by the integration of a tiered development system and performance-based financing, where the amount of da'wah incentives is directly linked to the productivity of the development, which is reported periodically. This pattern makes financing not only operational assistance but also an instrument for monitoring and evaluating da'wah performance. However, the sustainability of the program is still overshadowed by limited independent funding, the vast service area, and the digital literacy gap. This study confirms that the effectiveness of an organization's da'wah is highly dependent on the extent to which development and financing are managed as an integrated system, rather than two separate functions.